Pemberdayaan Kader dan Edukasi Masyarakat dalam Pencegahan Komplikasi Diabetes Mellitus - Nurul Hidayah; Widya Puspitasari; Rifaatul Laila Mahmudah; Nurwidji (Jurnal Pengabdian Masyarakat, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease that may cause various complications when it is not properly managed. The problems identified in Sumberporong Village were limited community knowledge regarding the prevention of DM complications and the suboptimal involvement of health cadres in educating and assisting residents. This community service activity aimed to empower health cadres and improve community knowledge regarding the prevention of DM complications. A participatory approach was used through preparation, cadre role orientation, community health education, interactive discussion, random blood glucose (RBG) screening, and knowledge evaluation using pre-test and post-test instruments. The activity involved 18 participants, consisting of 2 health cadres and 16 community members. The participants' mean knowledge score increased by 28.6 points, from 58.3 in the pre-test to 86.9 in the post-test. RBG screening showed that 8 participants (44.4%) had values of 125-145 mg/dL, 5 participants (27.8%) had values of 170-195 mg/dL, and 5 participants (27.8%) had values of 210-260 mg/dL. These findings indicate a short-term increase in knowledge after the educational activity and highlight the need for follow-up examination among participants with elevated RBG results. Cadre empowerment should be continued through mentoring, educational materials, and coordination with local health care facilities to support sustainable community education and monitoring